Awareness of Rural and Urban Youth Towards Female Foeticide - Priyanka,; Arya, Prasanlata (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted in Bikaner district of Rajasthan, India during November 2019–May 2020 to assess the awareness of rural and urban youth towards female foeticide and to find out the relationship of socio-economic characteristics of respondents with their awareness in Bikaner district of Rajasthan, India. Two panchayat samiti were selected based on highest sex ratio i.e., Sridungargarh and lowest sex ratio i.e., Kolayat. Bikaner city was divided into two zone i.e., east, and west. Out of them one ward was selected randomly from each zone i.e., ward number 60 was from east zone and ward number 44 was from west zone. A total of 200 respondents were selected for the study purpose. Questionnaire method was used for collecting data from the respondents. The result showed that all the respondents knew about the meaning of female foeticide, sex of the foetus could be determined before birth, female foeticide affects the society and repetitive abortion was hazardous to health of the female. The 25% respondents knew about overall sex ratio of Rajasthan and father was responsible for the sex of the child, 22% mother was responsible and only 14.5% of the respondents were aware about law related to PC- PNDT and MTP Act. The result showed that the 64% of the respondents had medium awareness level, while 21 and 15% of the respondents had low and high level of awareness about female foeticide.